Bunker conversion and the overcoming of siege mentality. Issue 7 (10th November 2017) - Morgan, Diane
ABSTRACT: This article is concerned with the function creativity can play in the cultural reinscription of war bunkers. It engages with theories of historiography, and practices of peacemaking, to consider whether aesthetic activity can be a potentially resistant force against militarism and 'siege mentality'.